Exploring the impact of artificial intelligence on teaching and learning in higher education - Stefan A. D. Popenici; Sharon Kerr (The Asia-Pacific Society for Computers in Education (APSCE), 2017)
Abstract This paper explores the phenomena of the emergence of the use of artificial intelligence in teaching and learning in higher education. It investigates educational implications of emerging technologies on the way students learn and how institutions teach and evolve. Recent technological advancements and the increasing speed of adopting new technologies in higher education are explored in order to predict the future nature of higher education in a world where artificial intelligence is part of the fabric of our universities. We pinpoint some challenges for institutions of higher education and student learning in the adoption of these technologies for teaching, learning, student support, and administration and explore further directions for research.